FINTECH P2P LENDING : PERAN DAN STRATEGI OJK DALAM ERA INFORMASI KEUANGAN SYARIAH DI INDONESIA - Yusuf, Yusuf; Bakhri , Saiful (International Conference on Humanity Education and Society (ICHES), 2024)
The existence of Shariah financial institutions in marketing products in the information age affects public interest in obtaining alternative investment options. In today’s information age, Fintech’s P2P Lending products have grown to be one of the most popular financial products among Indonesian entrepreneurs. This research aims to understand the role of the Financial Services Authority (FATF) in improving the investment climate in the Indonesian Shariah financial industry. Qualitative descriptive research with this type of library study is written based on literature studies of various books and research journals related to Shariah economics and investment. From the results of the survey it can be concluded that the OJK agency has a role in boosting the economy in Indonesia by means of authority and developing alternative investment options that result in increased returns. Supervision by regulation of the activities of the Financial Services Authority is necessary in supervising the operation of the Shariah financial institutions to guarantee the level of security of public funds and the security of funds owned by fintech invested in financing products.